FEATURES OF THE AEROBIC ENERGY SUPPLY SYSTEM AS A RESULT OF THE ACTIVITY OF THE CARDIORESPIRATORY SYSTEM - Vanyushin, Yu.S.; Elistratov, D.E.; Fedorov, N.A.; Rakhimov, M.I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the features of the aerobic energy supply system as a result of the activity of the cardiorespiratory system, depending on the age of athletes involved in cyclic sports, during bicycle ergometric testing. Methods and structure of the study. The subjects were athletes involved in endurance sports and, depending on age, the following groups of subjects were formed: 15-16 years old, 17-21 years old, 22-35 years old and 36-60 years old. All of them performed work on a bicycle ergometer with a power of 50, 100, 150 and 200 watts. Each stage of the load lasted 3 minutes, during which the differential rheogram according to Kubizek was recorded, modified by Yu.S. Vanyushin et al., and the indicators of the cardiovascular system were determined: heart rate, stroke volume, minute volume of blood circulation. With the help of a pneumotachograph, indicators of external respiration were determined: respiratory rate, tidal volume, minute respiratory volume. The oxygen utilization coefficient was calculated according to the generally accepted formula. Results and conclusions. A comprehensive study of the process of adaptation of the cardiorespiratory system of athletes of different ages involved in endurance sports allowed us to identify the possibilities of the aerobic method of energy supply, which depends on the age of the athletes. In athletes aged 15-16 and 36-60 years, according to the results of our research, it is advisable to develop an external respiration system aimed at increasing the minute volume of respiration, since in this case the aerobic method of energy supply functions better. Athletes aged 17-21 years should develop a circulatory system that increases the performance of the pumping function of the heart (stroke volume, minute volume of blood), which affects the ability of the heart to eject a larger volume of blood. This will have a positive effect on the aerobic way of energy supply. Athletes aged 22-35 years should stimulate the gas exchange function associated with an increase in the oxygen utilization factor (UFО2), which is the most optimal. In athletes of this age, apparently, it is advisable to develop this particular method of energy supply.